Migration, Social Structure and Economic Interdependence in Nepal: A Sociological Input-Output Analysis - Rai, Nara Dev (DMC Journal, 2025)
This article examines the interrelationships among migration, social structure, and economic interdependence in Nepal through a sociological input–output analytical framework. Migration has become a central livelihood strategy for a large segment of the Nepalese population, profoundly shaping household economies, community relations, and national development patterns. Drawing exclusively on secondary sources—including census data, academic literature, policy reports, and publications by international organizations—the study analyzes how labor out-migration and remittance inflows operate as key structural inputs that generate multiple social and economic outputs across different levels of society. The findings reveal that migration is deeply embedded within Nepal’s hierarchical social structure and is strongly mediated by caste, class, gender, and regional inequalities. While remittances have contributed to poverty reduction, improved household welfare, and short-term economic stability, their social and economic impacts are uneven and often contradictory. Migration has altered gender roles, household authority, and community institutions, yet it frequently reproduces existing forms of social stratification and creates new hierarchies based on migration success. At the macro level, remittance-led growth has strengthened consumption and service-sector expansion but has also generated structural dependency on external labor markets and constrained domestic productive transformation. By applying a sociological input–output perspective, the article moves beyond fragmented economic or social explanations and highlights the systemic and relational nature of migration in Nepal. The study contributes to migration and development scholarship by demonstrating how migration simultaneously functions as a mechanism of social stability and a constraint on long-term structural change. It concludes by emphasizing the need for integrated and equity-oriented policy interventions to ensure that migration contributes to inclusive and sustainable development in Nepal.